2021
DOI: 10.1038/s41467-021-25946-0
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody seroprevalence and associated risk factors in an urban district in Cameroon

Abstract: The extent of SARS-CoV-2 circulation in many African countries remains unclear, underlining the need for antibody sero-surveys to assess the cumulative attack rate. Here, we present the results of a cross-sectional sero-survey of a random sample of residents of a health district in Yaounde, Cameroon, conducted from October 14 to November 26, 2020. Among the 971 participants, the test-adjusted seroprevalence of anti-SARS-CoV-2 IgG antibodies was 29·2% (95% CI 24·3–34·1). This is about 322 times greater than the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
40
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 32 publications
13
40
2
1
Order By: Relevance
“…Despite their importance, differences in detection kits can complicate comparison of seroprevalence data from different parts of the continent. Nwosu et al [ 131 ] reported an antibody seroprevalence of up to 30% from sampling over 900 persons in Yaounde district, Cameroon, and this was more than 300 times the reported national case count from PCR testing. A study in Ghana with rapid kit detection of anti-nucleocapsid protein IgG and IgM reported up to 27% antibody seropositivity in populated areas such as lorry stations and markets, as compared to 10% seropositivity in shopping malls mostly patronized by the affluent [ 132 ], and these are much more than the reported infection rate from national case counts.…”
Section: Covid-19 Seroepidemiology In Africa and The Effect Of Co-inf...mentioning
confidence: 99%
“…Despite their importance, differences in detection kits can complicate comparison of seroprevalence data from different parts of the continent. Nwosu et al [ 131 ] reported an antibody seroprevalence of up to 30% from sampling over 900 persons in Yaounde district, Cameroon, and this was more than 300 times the reported national case count from PCR testing. A study in Ghana with rapid kit detection of anti-nucleocapsid protein IgG and IgM reported up to 27% antibody seropositivity in populated areas such as lorry stations and markets, as compared to 10% seropositivity in shopping malls mostly patronized by the affluent [ 132 ], and these are much more than the reported infection rate from national case counts.…”
Section: Covid-19 Seroepidemiology In Africa and The Effect Of Co-inf...mentioning
confidence: 99%
“… Overall seroprevalence of SARS-CoV-2 antibodies in Africa [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. …”
Section: Figureunclassified
“…15,22,23 Access to hospital care is limited and varies within and across countries and regions. 24,25 The burden of SARS-CoV-2 infection, including severe disease requiring hospitalization, is underestimated in sub-Saharan Africa [26][27][28] and is potentially more underestimated among children, who are less likely to be evaluated for infection. 15 To address this issue, the present study assessed clinical manifestations, outcomes, and factors associated with outcomes among children and adolescents hospitalized with COVID-19 in 6 countries in sub-Saharan Africa.…”
mentioning
confidence: 99%